2014
DOI: 10.1590/bjpt-rbf.2014.0050
|View full text |Cite
|
Sign up to set email alerts
|

Influences of hand dominance on the maintenance of benefits after home-based modified constraint-induced movement therapy in individuals with stroke

Abstract: Objective:To investigate the influence of hand dominance on the maintenance of gains after home-based modified constraint-induced movement therapy (mCIMT). Method:Aprevious randomized controlled trial was conducted to examine the addition of trunk restraint to the mCIMT. Twenty-two chronic stroke survivors with mild to moderate motor impairments received individual home-based mCIMT with or without trunk restraints, five times per week, three hours daily over two weeks. In this study, the participants were sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…When the cohort was divided into 2 groups, the median scores for the motor and sensory abilities and functional ability of the affected dominant UE were not statistically significant different than the affected nondominant UE. These findings support previous studies of 22 participants with subacute stroke 36 and 93 participants with chronic stroke. 13 Significant improvements between T1 and T2 were seen in motor and functional ability, daily use, and perceived recovery in both affected UEs.…”
Section: Discussionsupporting
confidence: 92%
“…When the cohort was divided into 2 groups, the median scores for the motor and sensory abilities and functional ability of the affected dominant UE were not statistically significant different than the affected nondominant UE. These findings support previous studies of 22 participants with subacute stroke 36 and 93 participants with chronic stroke. 13 Significant improvements between T1 and T2 were seen in motor and functional ability, daily use, and perceived recovery in both affected UEs.…”
Section: Discussionsupporting
confidence: 92%
“…To achieve this, trunk stability is needed for maintaining balance and posture while moving the upper extremity [ 12 ]. However, stroke patients have reduced trunk stability, resulting in the upper extremity being unable to reach the target, compensation for flexion, rotation of the trunk to compensate for insufficient distances, and reduced circumstances in which the shoulders and elbows can vary in length [ 13 ]. Decreased trunk stability in stroke patients is also a problem when performing upper extremity training with visual feedback [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that having a stroke affecting the dominant hand might be associated with unfavourable functional outcomes at the acute stage. However, in subacute and chronic phases, it is suggested that there is no significant difference in functional improvement among individuals with dominant or non‐dominant paralyses post‐stroke (Lima et al, ; Nam et al, ; Daou et al, ). Using client‐centred tools such as Canadian occupational performance measure (COPM), individuals post‐stroke tend to setup rehabilitation goals influenced by their stroke severity more than their handedness (Waddell et al, ).…”
Section: Introductionmentioning
confidence: 99%